Shared Decision Making for Athletes with Cardiovascular Disease: Practical Considerations. Issue 3 (March 2019) - Baggish, Aaron L.; Ackerman, Michael J.; Putukian, Margot; Lampert, Rachel
Abstract : The diagnosis and management of cardiovascular disease (CVD) in competitive athletes represent a fundamental responsibility of the sports medicine community. Following the diagnosis of a CVD in a competitive athlete, it is the responsibility of the sports medicine team to delineate an effective treatment and management strategy that places the health and wellness of the athlete as the primary objective. An essential and often challenging aspect of this process is determining the appropriateness of continued participation ( i.e., "return-to-play") in competitive athletics. Recently, a joint American Heart Association and American College of Cardiology Scientific Statement delineating sports eligibility supports a more patient-centered care model that supports shared decision making for clinicians and their patients/families. The present document was written to summarize the changing sports cardiology landscape with an aim of providing the cardiology and sports medicine communities with some practical approaches to eligibility decision making for competitive athletes with heart disease.